Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica) - Àngel, Joan J. Soto; Cantero, Álvaro L. Peña (Zootaxa, 2019)
Hydrozoans are a conspicuous component of Antarctic benthic communitites. Recent taxonomic effort has led to a substantial increase in knowledge on the diversity of benthic hydroids from some areas of the Southern Ocean, including the Weddell Sea, the largest sea in the Antarctic region. However, the study of many hydrozoan taxa are still pending, and the diversity in this huge region is expected to be higher than currently known. In order to contribute to the knowledge of taxonomy, ecology and distribution of these cnidarians, a study of unpublished material collected by several German Antarctic expeditions aboard the RV Polarstern in the eastern sector of the Weddell Sea has been conducted. A total of 77 species belonging to 22 families and 28 genera of benthic hydroids have been inventoried, constituting the most prolific collection hitherto analyzed. Most species (81%) belong to Leptothecata, but the observed share of Anthoathecata (19%) is higher than in previous Antarctic hydrozoan studies. Symplectoscyphidae was the most speciose family with 16 representatives (22%), followed by Haleciidae with 10 (14%) and Staurothecidae with 8 (11%). The number of species known in the area was increased with 27 new records, including several species rarely documented. As a result, the Weddell Sea becomes the second Antarctic region in terms of hydrozoan diversity, with 89 species known to date. Novel data on the use of substrate, reproductive phenology, and bathymetric range are provided for the inventoried species.